Effects of Tailings Gradation on Rheological Properties of Filling Slurry - Bingwen Wang; Tingyong Xiong; Lijing Gao; Yuepeng Chai; Xiangyu Cui; Wei Ding (Advances in Civil Engineering)
The key technology in filling mining is the gravity transportation of high-density slurries, and the filling system design is a significant part of this technology. The filling effect depends on the fluidity of the filling slurry. To investigate the influence of the gradation of tailings on the rheological properties of the filling slurry, this study uses particle size analysis to prepare three types of tailings: powder-, relatively fine-, and fine-grained tailings, which are then mixed in different proportions. The rheological properties of the resulting filling slurries are tested; the viscosity coefficients and yield stresses of the slurries are obtained using the analysis software provided with the MCR102 advanced rheometer that is used to measure the rheological properties of the slurries. The experimental results demonstrate that there is no absolute relationship between the rheological properties of the slurry and the size of the tailings particles, but the rheological properties are related to the gradation of tailings. Lubricating effect is weakened with an insufficient content of powder-grained particles in the tailings. On the contrary, when the content of powder-grained particles in the tailings is too high, the viscous substances in the slurry increase. Both of these conditions can increase the friction loss of the slurry.